2007
DOI: 10.1128/jcm.01984-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Epidemic European Fusidic Acid-Resistant Impetigo Clone of Staphylococcus aureus

Abstract: Resistance to the antibiotic fusidic acid in European strains of Staphylococcus aureus causing impetigo has increased in recent years. This increase appears to have resulted from clonal expansion of a strain we have designated the epidemic European fusidic acid-resistant impetigo clone (EEFIC), which carries the fusidic acid resistance determinant fusB on its chromosome. To understand better the properties of the EEFIC responsible for its success, we have performed detailed phenotypic and genotypic characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 37 publications
3
80
1
Order By: Relevance
“…These strains commonly cause staphylococcal scalded skin syndrome and bullous impetigo (28,43), toxin-mediated staphylococcal diseases which are associated with eta or etb in 65 to 100% of the cases (10,18,26,30,60). One such CC121 clone, characterized by ST123 and spa type t171, is notorious as the "epidemic European fusidic acid-resistant impetigo clone (EEFIC)" (27-29, 42, 44, 52).…”
Section: Discussionmentioning
confidence: 99%
“…These strains commonly cause staphylococcal scalded skin syndrome and bullous impetigo (28,43), toxin-mediated staphylococcal diseases which are associated with eta or etb in 65 to 100% of the cases (10,18,26,30,60). One such CC121 clone, characterized by ST123 and spa type t171, is notorious as the "epidemic European fusidic acid-resistant impetigo clone (EEFIC)" (27-29, 42, 44, 52).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described that the topical use of this drug has led to an increase of resistance. [20][21][22] Some suggest that a S. aureus clone responsible for the resistance to fusidic acid is spreading, 22,23 and that this is resulting in increased resistance. An earlier study in the Netherlands from 2002 showed no resistance to fusidic acid among impetigo isolates.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The fusB determinant originally was found on the plasmid pUB101 in S. aureus (26). Later, the fusB determinant also was found on a transposon-like element (27) or in a staphylococcal pathogenicity island (29).…”
mentioning
confidence: 99%